Kajian Filosofis Tentang Konsep Pendidikan di Era Klasik dan Pertengahan - Ali Ahmad Yenuri (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2017)
The concept of education is always interesting studied both from the classical era and the middle era, because the development of education is always dynamic because of the demands of the age will give birth to education in accordance with the era and era. In this study we will explore some educational concept from Al Qobisi to Al-Ghazali. With the thoughts of these figures hopefully make references in developing education in accordance with lately.Keywords; Education, al-Qobisi, al-Ghazali, Ikhwan As-Shafa